Whale shark, Rhincodon typus (Orectolobifoms: Rhincodontidae) feeding aggregations in Golfo Dulce, Osa Peninsula, Costa Rica. - Pacheco-Polanco, Juan Diego; Herra-Miranda, David; Oviedo-Correa, Lenin; Quirós-Pereira, Wagner; Figgener, Christine (Revista de Biología Tropical, 2015)
The zooplanktivorous whale shark (Rhincodon typus), is the largest living chondrichthyan and a cosmopolitan species, living in tropical, warm and temperate waters. It is considered vulnerable by the International Union for Conservation of Nature (IUCN), and is known for big aggregations in many parts of the world. These are associated with particular oceanographic features where primary productivity is thought to be high. For the first time, four whale shark feeding aggregations are documented in Golfo Dulce, Costa Rica, a tropical fjord-like embayment located in the south Pacific region of the country. Observations were made in January and August 2009, March 2012 and in January 2013, Estimated group structure and size remained constant over time with an equal proportion of adults and juveniles in the same area. These aggregations were observed on the north-western coast of Golfo Dulce’s inner basin, close to the Rincón and Tigre rivers. These two rivers are known to provide organic material which area important nutrients for the gulf zooplanktonic communities. During one of the observed feeding aggregations, copepods (Order: Calanoida) were seen in the water close to feeding individuals. Given the vulnerability of whale sharks, management decisions for Golfo Dulce need to include strategies to control tourism, boat circulation, commercial and sports fisheries and coastal development.